PENGARUH MANAJEMEN LABA RIIL TERHADAP KECURANGAN LAPORAN KEUANGAN - Ida Rahmawaty (2023)
This research aims to prove real earnings management through abnormal sales, abnormal production, and abnormal discretionary on financial statement fraud. Control variables in this research are leverage, firm size, and profitability. This research uses purposive sampling to determine samples. This research uses 46 companies listed in the Kompas 100 index during 2015-2020 as samples. This research is a quantitative research using secondary data from annual report. The research uses logistic regression analisys with data panel. In this research, real earnings management processed using STATA 16 and logistic regression analisys processed using IBM SPSS 26. The results shows that real earnings management have a insignificant influence on financial statement fraud. Real earnings management through abnormal sales has a insignificant positive influence on financial statement fraud. Real earnings management through abnormal production has a insignificant positive influence on financial statement fraud. Real earnings management through abnormal discretionary has a insignificant positive influence on financial statement fraud.